Peran Kepemimpinan dan Employee Engagement terhadap Kinerja Individual Karyawan Instalasi Farmasi - Rahayu, Susi A.; Surahman, Emma (Indonesian Journal of Clinical Pharmacy, 2012)
Ketidakpuasan karyawan terhadap kepala instalasi dapat menyebabkan kinerja karyawan menurun dan ketidakpuasan pelanggan. Salah satu caraÂ  meningkatkan kinerja karyawan adalah denganmerasa terikat terhadap pekerjaannya (employee engagement). Salah satu faktor untuk meningkatkanemployee engagement adalah faktor kepemimpinan. Oleh karena itu, perlu dilakukan penelitian mengenai pengaruh kepemimpinan terhadap kinerja individual karyawan instalasi farmasi rumah sakit serta pengaruh employee engagement sebagai mediator. Sebanyak 79 karyawan instalasi farmasi dari dua rumah sakit swasta di Kota Bandung menjadi partisipan. Penelitian ini menggunakan teknik partial least square untuk menguji hubungan hipotesis. Hasil penelitian menunjukkan terdapat signifikansi antara kepemimpinan terhadap employee engagement (t value (12,84) > t-tabel (1,64)), signifikansi employee engagement terhadap kinerja individual (t value (3,83) > t-tabel (1,64)). Kepemimpinan terhadap kinerja individual (t value (0,45) < t-tabel (1,64)) tidak terdapat pengaruh dan signifikansinya. Employee engagement memediasi hubungan antara kepemimpinan dan kinerja individual.Kata kunci: Kepemimpinan, employee engagement, kinerja individualÂ Role of Leadership and Employee Engagement towards Individual Performance of Pharmacy EmployeesAbstractEmployees dissatisfaction to the head of the hospital pharmacy will decrease employees performanceand unsatisfied customers. To solve the problems, employees should be based on performance as customer expectations in providing services. One of the ways to improve the performance of the employees, they must feel engage to the work. One of the factors to improve employee engagement isthe leadership factor. Therefore, it is necessary to study the impact of leadership on individual performance employee in hospital pharmacy and also the influence of employee engagement as a mediator. A total of 79 employees from the pharmacy in two private hospitals in Bandung became theparticipants. This study used the technique of partial least squares to test the hypothesized relationships.The results showed that there were significant between leadership to employee engagement (t value (12,84) > t-table (1.64)), the significance of employee engagement on individual performance (t value (3.83) > t-table (1.64)). In contrast, there was no influence and significance in leadership on individual performance (t value (0.45) < t-table (1.64)). Employee engagement fully mediated the relationshipbetween leadership and individual performance. Therefore, improving pharmacy services is a set of actions and involvement of pharmacy employees who are consistent, sustainable and clear. Key words: Leadership, employee engagement, individual performance